Lysosomal sequestration of sunitinib: a novel mechanism of drug resistance - Gotink, Kristy J; Broxterman, Henk J; Labots, Mariette; de Haas, Richard R; Dekker, Henk; Honeywell, Richard J; Rudek, Michelle A; Beerepoot, Laurens V; Musters, René J; Jansen, Gerrit; Griffioen, Arjan W; Assaraf, Yehuda G; et al. (Clinical cancer research, 2011)
Resistance to antiangiogenic tyrosine kinase inhibitors such as sunitinib is an important clinical problem, but its underlying mechanisms are largely unknown. We analyzed tumor sunitinib levels in mice and patients and studied sensitivity and resistance mechanisms to sunitinib. Intratumoral and plasma sunitinib concentrations in mice and patients were determined. Sunitinib exposure on tumor cell proliferation was examined. Resistant tumor cells were derived by continuous exposure and studied for alterations in intracellular sunitinib accumulation and activity. Intratumoral concentrations of sunitinib in mice and patients were 10.9 ± 0.5 and 9.5 ± 2.4 μmol/L, respectively, whereas plasma concentrations were 10-fold lower, 1.0 ± 0.1 and 0.3 ± 0.1 μmol/L, respectively. Sunitinib inhibited tumor cell growth at clinically relevant concentrations in vitro, with IC(50) values of 1.4 to 2.3 μmol/L. Continuous exposure to sunitinib resulted in resistance of 786-O renal and HT-29 colon cancer cells. Fluorescent microscopy revealed intracellular sunitinib distribution to acidic lysosomes, which were significantly higher expressed in resistant cells. A 1.7- to 2.5-fold higher sunitinib concentration in resistant cells was measured because of increased lysosomal sequestration. Despite the higher intracellular sunitinib accumulation, levels of the key signaling p-Akt and p-ERK 1/2 were unaffected and comparable with untreated parental cells, indicating reduced effectiveness of sunitinib. We report that sunitinib inhibits tumor cell proliferation at clinically relevant concentrations and found lysosomal sequestration to be a novel mechanism of sunitinib resistance. This finding warrants clinical evaluation whether targeting lysosomal function will overcome sunitinib resistance.